Randomized dose ranging study of the reduction of fasting and postprandial glucose in type 2 diabetes by nateglinide (A-4166). - Gribble, F; Manley, SE; Levy, J (2001)
OBJECTIVE: This randomized crossover double-blind placebo-controlled study aimed to assess the efficacy of nateglinide (A-4166), a novel phenylalanine-derived insulin secretagogue, in type 2 diabetic subjects while fasting and 5 min before a standard meal. RESEARCH DESIGN AND METHODS: A single dose of nateglinide (60, 120, or 180 mg) or placebo was given to eight diet-treated overnight-fasted type 2 diabetic patients and to seven patients 5 min before a standard breakfast. Plasma glucose, radioimmunoassay insulin, and nateglinide were measured at baseline and for a further 180 min. RESULTS: The time-averaged 180-min postdose mean decrease in fasting plasma glucose concentration was greater after nateglinide (1.8 mmol/l; 95% CI 1.5-2.0) than after placebo (0.7 mmol/l; 95% CI 0.3-1.2) (P < 0.001). Hypoglycemia did not develop in any of the subjects. Insulin concentrations increased 1.5-, 1.8-, and 1.9-fold with the 60-, 120-, and 180-mg doses, respectively (P < 0.001), peaking approximately 30 min after the dose. Nateglinide concentrations peaked after approximately 30 min, decreasing to 21% of peak by 180 min. In the meal test, the mean increase (2.9 mmol/l, 2.3-3.6) in plasma glucose over 180 min after placebo was reduced by 1.8 mmol/l (P < 0.001) with the two higher doses of nateglinide. CONCLUSIONS: A single dose of nateglinide administered to diet-treated type 2 diabetic patients with fasting hyperglycemia increased insulin secretion and reduced fasting glucose without hypoglycemia. Administered 5 min before a meal, nateglinide reduced the postprandial glucose excursion by 64%. With its rapid onset and short duration of action, nateglinide is a promising oral prandial therapy in type 2 diabetes.